Análisis de los métodos y resultados obtenidos del ciclo productivo del camarón en la línea de valor agregado - Alcívar Villamil, Sandro Renee (2024)
The purpose of this research topic is to provide a solution to the problems that the aquaculture sector presents within the processing plants, especially those that have the Value Added production line, which are caused by certain variables within the shrimp production process cycle, the deviations caused by quality, uniformities and differences in the counts requested by customers, which in one way or another reduce the profitability that could be obtained in sales if there is no adequate and correct shrimp classified. For this reason, it is important to recognize the entire process that is involved, logistics, planning, production, accounting and sales as main areas within this research process; and through the respective analysis and constructive intervention within the production process, using better economic and productive resources, for example, purchased shrimp, labor and installed capacity, in order to obtain better profitability at the time of sales, especially in Added Value, which is the most affected line, but at the same time, in which the greatest exploitation can be obtained, based on the variety of products resulting from its production processes, offering a wide variety of sizes, presentations and cuts that can satisfy the needs of customers around the world.